Prevalence and Progression of Late Gadolinium Enhancement in Children and Adolescents With Hypertrophic Cardiomyopathy. Issue 8 (21st August 2018) - Axelsson Raja, Anna; Farhad, Hoshang; Valente, Anne Marie; Couce, John-Paul; Jefferies, John Lynn; Bundgaard, Henning; Zahka, Kenneth; Lever, Harry; Murphy, Anne M.; Ashley, Euan; Day, Sharlene M.; Sherrid, Mark V.; et al.
Abstract : Background: Late gadolinium enhancement (LGE) on cardiac magnetic resonance imaging (CMR) is believed to represent dense replacement fibrosis. It is seen in ≈60% of adult patients with hypertrophic cardiomyopathy (HCM). However, the prevalence of LGE in children and adolescents with HCM is not well established. In addition, longitudinal studies describing the development and evolution of LGE in pediatric HCM are lacking. This study assesses the prevalence, progression, and clinical correlations of LGE in children and adolescents with, or genetically predisposed to, HCM. Methods: CMR scans from 195 patients ⩽21 years of age were analyzed in an observational, retrospective study, including 155 patients with overt HCM and 40 sarcomere mutation carriers without left ventricular (LV) hypertrophy. The extent of LGE was quantified by measuring regions with signal intensity >6 SD above nulled remote myocardium. Results: Patients were 14.3±4.5 years of age at baseline and 68% were male. LGE was present in 70 (46%) patients with overt HCM (median extent, 3.3%; interquartile range, 0.8–7.1%), but absent in mutation carriers without LV hypertrophy. Thirty-one patients had >1 CMR (median interval between studies, 2.4 years; interquartile range, 1.5–3.2 years). LGE was detected in 13 patients (42%) at baseline and in 16 patients (52%) at follow-up CMR. The median extent of LGE increased by 2.4 g/y (range, 0–13.2 g/y) from 2.9% (interquartile range, 0.8–3.2%) of LV mass to 4.3% (interquartile range, 2.9–6.8%) ( P =0.02). In addition to LGE, LV mass and left atrial volume, indexed to body surface area, and z score for LV mass, as well, increased significantly from first to most recent CMR. Conclusions: LGE was present in 46% of children and adolescents with overt HCM, in contrast to ≈60% typically reported in adult HCM. In the subset of patients with serial imaging, statistically significant increases in LGE, LV mass, and left atrial size were detected over 2.5 years, indicating disease progression over time. Further prospective studies are required to confirm these findings and to better understand the clinical implications of LGE in pediatric HCM. Abstract : Supplemental Digital Content is available in the text.